Comparison of AOMDV With and Without Black Hole Attack (International Journal of Engineering and Computer Science, 2015)
The popularity of MANETS is increasing day-by-day as users choose to connect to a network irrespective of their geographical position. Because of this exceptional feature of MANETs, they are open to a huge amount of malicious activity. Black Hole attack is one kind of threat in MANETs in which the data of the network is routed towards a node which drops all the packets entirely. In this paper we propose a feasible solution to find and prevent black hole attack that can be implemented using AMODV protocol. Also, to develop simulations to analyze the performance of proposed solution based on various security parameters like Packet Delivery Ratio with and without black hole.